Portrayal of caesarean section in Brazilian women's magazines: 20 year review. (25th January 2011) - Torloni, Maria Regina; Daher, Silvia; Betrán, Ana Pilar; Widmer, Mariana; Montilla, Pilar; Souza, Joao Paulo; Merialdi, Mario
Abstract : Objective To assess the quality and comprehensiveness of the information on caesarean section provided in Brazilian women's magazines. Design Review of articles published during 1988-2008 in top selling women's magazines. Setting Brazil, one of the countries with the highest caesarean section rates in the world. Data sources Women's magazines with the largest distribution during the study period, identified through the official national media indexing organisations. Selection criteria Articles with objective scientific information or advice, comments, opinions, or the experience of ordinary women or celebrities on delivery by caesarean section. Main outcome measures Sources of information mentioned by the author of the article, the accuracy and completeness of data presented on caesarean section, and alleged reasons why women would prefer to deliver though caesarean section. Results 118 articles were included. The main cited sources of information were health professionals (78% (n=92) of the articles). 71% (n=84) of the articles reported at least one benefit of caesarean section, and 82% (n=97) reported at least one short term maternal risk of caesarean section. The benefits most often attributed to delivery by caesarean section were reduction of pain and convenience for family or health professionals. The most frequently reported short term maternal risks of caesarean section were increased time to recover and that it is a less natural way of giving birth. Only one third of the articles mentioned any long term maternal risks or perinatal complications associated with caesarean section. Fear of pain was the main reported reason why women would prefer to deliver by caesarean section. Conclusions Most of the articles published in Brazilian women's magazines do not use optimal sources of information. The portrayal of caesarean section is mostly balanced, not explicitly in favour of one or another route of delivery, but incomplete and may be leading women to underestimate the maternal/perinatal risks associated with this route of delivery.